Spatial Organization of Superparamagnetic Iron Oxide Nanoparticles in/on Nano/Microsized Carriers Modulates the Magnetic Resonance Signal - Lee, Min Kyung (Langmuir : the ACS journal of surfaces and colloids, 2018)
Superparamagnetic iron oxide nanoparticles (SPIONs) are often encapsulated into drug-carrying nano/microsized particles for simultaneous magnetic resonance (MR) imaging and treatment of diseased tissues. Unfortunately, encapsulated SPIONs may have a limited ability to modulate the T2-weighted relaxation of water protons, but this insight has not been examined systematically. This study demonstrates that SPIONs immobilized on 200 nm diameter poly(lactic- co-glycolic acid) (PLGA) nanoparticles using Pickering emulsification present 18-fold higher relaxivity than encapsulated SPIONs and 1.5-fold higher relaxivity than free SPIONs. In contrast, the SPIONs immobilized on 10 μm diameter PLGA particles exhibit a minor increase in MR relaxivity. This interesting finding will significantly impact current efforts to synthesize and assemble advanced MR contrast agents